Comparison of antibiotic resistant Escherichia coli obtained from drinking water sources in northern Tanzania: a cross-sectional study. Issue 1 (December 2016) - Lyimo, Beatus; Buza, Joram; Subbiah, Murugan; Smith, Woutrina; Call, Douglas
Abstract Background Antimicrobial resistance (AMR) is a growing and significant threat to public health on a global scale.Escherichia coli comprises Gram-negative, fecal-borne pathogenic and commensal bacteria that are frequently associated with antibiotic resistance. AMRE. coli can be ingested via food, water and direct contact with fecal contamination. Methods We estimated the prevalence of AMREscherichia coli from select drinking water sources in northern Tanzania. Water samples (n  = 155) were collected and plated onto Hi-CromeE. coli and MacConkey agar. PresumptiveE. coli were confirmed by using auidA PCR assay. Antibiotic susceptibility breakpoint assays were used to determine the resistance patterns of each isolate for 10 antibiotics. Isolates were also characterized by select PCR genotyping and macro-restriction digest assays. Results E. coli was isolated from 71 % of the water samples, and of the 1819E. coli tested, 46.9 % were resistant to one or more antibiotics. Resistance to ampicillin, streptomycin, sulfamethoxazole, tetracycline, and trimethoprim was significantly higher (15–30 %) compared to other tested antibiotics (0–6 %;P  < 0.05). Of the β-lactam-resistant isolates, bla TEM-1 was predominant (67 %) followed bybla CTX-M (17.7 %) andbla SHV-1 (6.0 %). Among the tetracycline-resistant isolates, tet (A) was predominant (57.4 %) followed bytet (B) (24.0 %).E. coli isolates obtained from these water sources were genetically diverse with few matching macro-restriction digest patterns. Conclusion Water supplies in northern Tanzania may be a source of AMRE. coli for people and animals. Further studies are needed to identify the source of these contaminants and devise effective intervention strategies.